PPARγ agonist-loaded PLGA-PEG nanocarriers as a potential treatment for Alzheimer’s disease: in vitro and in vivo studies - Silva-Abreu M (Dove Medical Press, 2018)
Marcelle Silva-Abreu,1,2 Ana Cristina Calpena,1,2 Pol Andrés-Benito,3,4 Ester Aso,3,4 Ignacio A Romero,5 David Roig-Carles,5 Radka Gromnicova,5 Marta Espina,1,2 Isidre Ferrer,3,4 María Luisa García,1,2 David Male5 1Department of Pharmacy, Pharmaceutical Technology and Physical Chemistry, Faculty of Pharmacy and Food Sciences, University of Barcelona, Barcelona, Spain; 2Institute of Nanoscience and Nanotechnology (IN2UB), University of Barcelona, Barcelona, Spain; 3Servei d’Anatomia Patològica, Institut d’Investigació Biomèdica de Bellvitge-Hospital Universitari de Bellvitge, Universitat de Barcelona, L’Hospitalet de Llobregat, Spain; 4Centro de Investigación Biomédica en Red de Enfermedades Neurodegenerativas, Instituto de Salud Carlos III, Madrid, Spain; 5School of Life, Health and Chemical Sciences, Faculty of Science, The Open University, Walton Hall, Milton Keynes, UK Objective: The first aim of this study was to develop a nanocarrier that could transport the peroxisome proliferator-activated receptor agonist, pioglitazone (PGZ) across brain endothelium and examine the mechanism of nanoparticle transcytosis. The second aim was to determine whether these nanocarriers could successfully treat a mouse model of Alzheimer’s disease (AD). Methods: PGZ-loaded nanoparticles (PGZ-NPs) were synthesized by the solvent displacement technique, following a factorial design using poly (lactic-co-glycolic acid) polyethylene glycol (PLGA-PEG). The transport of the carriers was assessed in vitro, using a human brain endothelial cell line, cytotoxicity assays, fluorescence-tagged nanocarriers, fluorescence-activated cell sorting, confocal and transmission electron microscopy. The effectiveness of the treatment was assessed in APP/PS1 mice in a behavioral assay and by measuring the cortical deposition of β-amyloid. Results: Incorporation of PGZ into the carriers promoted a 50x greater uptake into brain endothelium compared with the free drug and the carriers showed a delayed release profile of PGZ in vitro. In the doses used, the nanocarriers were not toxic for the endothelial cells, nor did they alter the permeability of the blood–brain barrier model. Electron microscopy indicated that the nanocarriers were transported from the apical to the basal surface of the endothelium by vesicular transcytosis. An efficacy test carried out in APP/PS1 transgenic mice showed a reduction of memory deficit in mice chronically treated with PGZ-NPs. Deposition of β-amyloid in the cerebral cortex, measured by immunohistochemistry and image analysis, was correspondingly reduced. Conclusion: PLGA-PEG nanocarriers cross brain endothelium by transcytosis and can be loaded with a pharmaceutical agent to effectively treat a mouse model of AD. Keywords: nanoparticle, Alzheimer’s disease, blood–brain barrier, brain endothelium, pioglitazone, APP/PS1 transgenic mouse